Identifying Material Accumulation Processes in Drinking Water Distribution Systems with Extended Period EPANET MSX Turbidity Simulations. (2015) - Husband, S.; Jackson, M.; Boxall, J.
Abstract: Discolouration is an international phenomenon in drinking water distribution systems due to erosion of particulate material layers. In the UK water companies are implementing hydraulic layer conditioning for maintenance and resilience with significant cost benefits, despite limited understanding of the material accumulation processes. In this paper 18 months turbidity data from a 4 km trunk main is simulated using four extended period Epanet MSX model formulations. The measured data demonstrates recurrent regeneration of discolouration risk and hydraulic conditioning as pro-active mitigation. Modelling facilitates investigation of layer regeneration processes, helping inform future discolouration models and operational strategies to safeguard water quality.